METHODOLOGICAL TRAINING SYSTEM OF FUTURE TEACHERS FOR SPECIALIZED TEACHING AND ITS STRUCTURE - Saipov, Amangeldi; Kamalov, Yusubali; Kamalov, Murat; Uzakhova, Ainagul; Kendzhaeva, Balnur (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
At present, the system of teacher training for future teachers being formed does not take into account the true nature of the methodological assistance that arises in the process of solving various practical tasks of the teacher. Our research is dedicated to form a methodological preparation system of future teachers for specialized teaching in curricular and extracurricular teaching processes. In the current paper we list the opportunities for learning, teaching and learning, as well as the presence of a leading contradiction between the unidentified functional features of the components that form the methodological system for the training of future teachers in curricula and outside the learning process. Thus, scientifically formulated methodological training allows future teachers to adapt to various changes in their professional assistance, skillfully apply teaching methods and use them by changing, using traditional and innovative approaches flexibly within their pedagogical "laboratory" framework to combine methodological knowledge and skills.Purpose of the study: To develop a system of methodological training of future professional education teachers in the process of study and out-of-class learning and to describe their functional components.Research Methods: studying of the mechanism of conditions in the field of globalization, preservation of the originality, cultural values, customs, traditions, expressing the importance of self-determination.Practical value: According to the system of methodological training provided, the future teacher develops methodological knowledge, business and skill based on subject and metaphorically developed functional character.